2022
DOI: 10.3846/jeelm.2022.16303
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Genetic and Environmental Characteristics of Lithuanian Populations of Purple Loosestrife (Lythrum Salicaria)

Abstract: The present study evaluated genetic diversity of Lithuanian populations of Lythrum salicaria in relation to parameters of riparian environment. Growing along Nemunas, Seaside and Lielupė river basins, 15 populations were examined using amplified fragment length polymorphism markers. Molecular data were related to the river basins, type of land use and cover, natural vice versa regulated fragments of the rivers. Population mean genetic diversity parameters were as follows: percentage of polymorphic loci (57.2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…In the present study, statistically significant relations (Mantel tests) were found among geographic and genetic distances up to 8416 km of Eurasian populations (Figure 1), similar to Jakubowski et al's [56] assessments of Eurasian populations within a distance up to 1000 km and European populations within distances to 250 km [58]. Mantel tests revealed a significant correlation among genetic and geographic distances of Lithuanian populations of naturally growing Lythrum salicaria [73] or invasive Echinocystis lobata [77], both supporting the theory that this exotic species is currently naturally spreading along the riverbanks.…”
Section: Interpopulation Variabilitysupporting
confidence: 90%
“…In the present study, statistically significant relations (Mantel tests) were found among geographic and genetic distances up to 8416 km of Eurasian populations (Figure 1), similar to Jakubowski et al's [56] assessments of Eurasian populations within a distance up to 1000 km and European populations within distances to 250 km [58]. Mantel tests revealed a significant correlation among genetic and geographic distances of Lithuanian populations of naturally growing Lythrum salicaria [73] or invasive Echinocystis lobata [77], both supporting the theory that this exotic species is currently naturally spreading along the riverbanks.…”
Section: Interpopulation Variabilitysupporting
confidence: 90%
“…For various plant species, including junipers, Ellenberg indicator values (EIV) of neighboring herbaceous plant species are widely used to evaluate environment in the sites without the need to perform physico-chemical measurements [ 73 , 74 , 75 , 76 , 77 ]. During evaluation of J. communis environments by EIV, the soil richness in nutrients (EIV-N) [ 35 ] showed low fertility for all habitats; it was lower than the middle value (5) and ranged in the interval of 2.7 to 4.4.…”
Section: Discussionmentioning
confidence: 99%
“…To relate ionomic data with other characteristics of J. communis , the genetic diversity of juniper populations was evaluated using ISSR markers [ 39 ]. For comparison of ionomic data with environmental parameters, undergrowth trees and shrubs, herbaceous species, and dwarf shrubs were recorded at each site following Braun-Blanquet [ 90 ] and the abundance of each species was evaluated using EIV [ 35 ] as described in detail previously [ 72 , 75 , 76 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genetics in this system have thus far only been studied with methods that have limited reproducibility or low resolution ( Strefeler et al . 1996 a, b ; Houghton-Thompson et al 2005 ; Kubátová et al 2008 ; Chun et al 2009 ; Middleton et al 2019 ; Jocienė et al 2022 ), which—along with hybridization—leave Lythrum taxonomy largely unresolved. As genetic tools become increasingly accessible, biologists are creating a more generalized understanding rapid evolution in introduced species.…”
Section: Discussionmentioning
confidence: 99%